PENERAPAN MANAJEMEN KEUANGAN SEKOLAH DI SMP NEGERI 1 BAJENG KABUPATEN GOWA - Fadilah, Nurul; M. Ikhwan Maulana Haeruddin; Nurman (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
This study aims to determine the mechanism for implementing school financial management at SMP Negeri 1 Bajeng, Gowa Regency. The type of research used in this research is descriptive qualitative with data collection methods through observation, interviews and documentation studies. The data management and data analysis techniques used are data reduction, data presentation and drawing conclusions. The results of this study indicate that the implementation of educational financial management at SMP Negeri 1 Bajeng, Gowa Regency can be carried out in a controlled and effective manner, especially in terms of financial allocation. Although in practice there are still some obstacles experienced by the school. The school education financial management system is implemented with reference to the preparation of the RKAM. The mechanism for implementing educational financial management at SMP Negeri 1 Bajeng includes financial planning, and auditing and financial accountability. With the creation of the RKAM that has been produced by the school during the annual work meeting, this is very helpful and supports the school in achieving the maximum success of each implementation of educational operational activities. The ability of human resources owned by SMP Negeri 1 Bajeng is a supporting factor for the school in overcoming obstacles that occur due to existing financial conditions with priority and unexpected financial expenditures/allocations